The Influence of Intellectual Capital, Learning Capability, and Technological Orientation on the Innovation Capability and Sustainable Competitive Advantage of Batik SMEs in Indonesia - Utomo, Bangun Prajadi Cipto; Sentosa, Ilham; Osman, Sharina; Santosa, Tri Djoko (JINAV: Journal of Information and Visualization, 2024)
In industries that produce environmental waste, concern for environmental sustainability is the main requirement to achieve business sustainability. Apart from environmental problems, in an era of increasingly fierce industrial competition, innovation capability is a factor that influences a company's competitive advantage in winning market competition. This study investigates the antecedents of innovation capabilities and sustainable competitive advantage in Batik SMEs in Indonesia. The population in this research is the small and medium-scale batik industry in the Solo Raya area. The number of samples taken was 113 respondents and determined using the purposive sampling method. The results of this study found that intellectual capital, learning ability, and technological orientation directly affect innovation ability and indirectly affect the sustainable competitive advantage of Batik SMEs in Indonesia. The ability to innovate directly influences the sustainable competitive advantage of Batik SMEs in Indonesia.